Begravelserne i kapellet ved Spidlegård - Heide, Poul Baltzer (Hikuin, 2003)
The Burials in the chapel by Spidlegård By Poul Baltzer Heide The purpose of this anthropological research is an attempt to find a pattern in the burials, in factors such as sex, age and disease. Because of the poor possibilities to decide the sex of the buried, no convincing image of this factors relevance can be drawn. On the contrary, age could be estimated in 80 % of the cases, hereof five were children. The average age appeared to be 42.4 years, with a moderate spreading on both sides. The age-interval spans between approximately 18 and 75 years. Symptoms of leprosy was only to be found on four individuals. This circumstance suggests that the right to be buried inside the chapel was limited to the superiors of the hospital. However, this does not explain the five children, and therefore it is possible that these are the result of a system where the whole family moved to the hospital if one of the parents got leprous. The placing of the graves can partially be reconstructed using the notes made on the original research-schedules by Vilh. Møller-Christensen. 14 of the burials are mentioned, and can be divided into six coherent groups, of which three cab be related to the remainings of the foundations. Considering the dating of the burials, the only clue comes from the arm positions, who points at the 14th century. The coins cannot be used to date the burials, since none of them for sure are related to the buried.